Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-51107
|View full text |Cite
|
Sign up to set email alerts
|

CFD Investigation on the Circumferential Grooves Casing Treatment of Transonic Compressor

Abstract: The performance of NASA Rotor 37 with Circumferential Grooves Casing Treatment (CGCT) is studied with an in-house CFD code NSAWET. Based on the stall mechanism analysis, a number of CGCT configurations have been proposed and numerically tested. The computation results show that the stall mechanisms are strongly related with the width of tip clearance. With a small tip clearance, the stall process is dominated by the trailing edge separation, while the leading edge tip leakage vortex breakdown induced blockage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
1
21
1
Order By: Relevance
“…The numerical methods adopted have been validated against Rotor 37 in the references [5,6], thus the details are omitted in this paper.…”
Section: Configuration and Numerical Methodsmentioning
confidence: 99%
“…The numerical methods adopted have been validated against Rotor 37 in the references [5,6], thus the details are omitted in this paper.…”
Section: Configuration and Numerical Methodsmentioning
confidence: 99%
“…When the CGCT is adopted, the flux exchange between the groove-casing interfaces are dealt with using an overlap-area weighted reconstruction method [31]. The accuracy of NSAWET as applied to turbomachinery has been validated by previous studies [24,32,33].…”
Section: Methodsmentioning
confidence: 99%
“…The width of each groove consists of ten percent axial chord tip and the gap between two grooves was five percent of the axial chord tip. Previous Researchers (Huang et al, 2008;Kim et al, 2012) researched on the rectangular grooves depth, tip clearance and width to find the effects of these factors on stall margin. They revealed that using CGCT could enhance the performance and stable range of the axial flow compressor.…”
Section: Design and Illustration Of Cgctmentioning
confidence: 99%
“…Shabbir et al (2005) worked on low-speed rotor to check the CGCT physical mechanism with the analysis of the budget of axial momentum equation. Huang et al (2008) worked on the circumferential grooves' width and depth casing treatment to improve the stall margin and performance using numerical analysis and they proposed that mechanism of the stall was significantly affected by clearance tip. Khan et al (2011) worked on the CGCT, tip recess and combined model of both to evaluate the behavior of stall of NASA rotor 37.…”
Section: Introductionmentioning
confidence: 99%